Executive Functions and the Improvement of Thinking Abilities: The Intervention in Reading Comprehension - García-Madruga, Juan A.; Gómez-Veiga, Isabel; Vila, José Ó. (Frontiers in Psychology, 2016)
In this paper, we propose a preliminary theory of executive functions that address in a specific way their relationship with working memory (WM) and higher-level cognition. It includes: a) four core on-line WM executive functions that are involved in every novel and complex cognitive task; b) two higher order off-line executive functions, planning and revision, that are required to resolving the most complex intellectual abilities; and c) emotional control that is involved in any complex, novel and difficult task. The main assumption is that efficiency on thinking abilities may be improved by specific instruction or training on the executive functions necessary to solving novel and complex tasks involved in these abilities. Evidence for the impact of our training proposal on WM´s executive functions involved in higher-level cognitive abilities comes from three studies applying an adaptive program designed to improve reading comprehension in primary school students by boosting the core WM´s executive functions involved in it: focusing on relevant information, switching (or shifting) between representations or tasks, connecting incoming information from text with long-term representations, updating of the semantic representation of the text in WM, and inhibition of irrelevant information. The results are consistent with the assumption that cognitive enhancements from the training intervention may have affected not only a specific but also a more domain-general mechanism involved in various executive functions. We discuss some methodological issues in the studies of effects of WM training on reading comprehension. The perspectives and limitations of our approach are finally discussed.